AB11O16(OH)2 (A = K and Cs): interpenetrating 2D layers with large birefringence. Issue 1 (16th December 2020) - Chen, Zhen; Guo, Jingyu; Han, Shujuan; Zeng, Hao; Yang, Zhihua; Pan, Shilie
Abstract : By a cation substitution strategy, two new hydroxyborates AB11 O16 (OH)2 (A = K and Cs) were synthesized, and KB11 O16 (OH)2 exhibits a short DUV cutoff edge (195 nm) and a large birefringence. Abstract : Two new isostructural alkali metal hydroxyborates, AB11 O16 (OH)2 (A = K and Cs), with two-dimensional (2D) interpenetrating [B11 O18 (OH)2 ]∞ layers have been successfully obtained. The calculated birefringences of KB11 O16 (OH)2 and CsB11 O16 (OH)2 are 0.104 and 0.100 at 546 nm, respectively. Moreover, KB11 O16 (OH)2 exhibits a short DUV cutoff edge (195 nm).